Monos = Monkeys - Canizares, Susan, 1960-; Chanko, Pamela, 1968- (New York : Scholastic, 2002)
Photographs and simple text explore the daily activities of monkeys in the Amazon rainforest.
Keywords: Monkeys -- Juvenile literature; Monkeys; Spanish language materials -- Bilingual